International standards for IgG and IgM anti-β2glycoprotein antibody measurement. (October 2014) - Willis, R; Grossi, C; Orietta Borghi, M; Martos-Sevilla, G; Zegers, I; Sheldon, J; Meroni, PL
International standards for anti-beta2 glycoprotein I (anti-β2 GPI) testing are needed. We evaluated the suitability of polyclonal/monoclonal candidate reference materials (RM) for the assay. IgG/IgM anti-β2 GPI were affinity-purified (AP) from high-positive antiphospholipid syndrome sera and IgG from HCAL clone supernatant. Igs were tested for purity by SDS-PAGE, pooled, concentrated, sterile-filtered and the protein concentration determined. One unit was defined as the binding activity of 1 µg/ml of AP anti-β2 GPI Ig. IgG/IgM RM were each assigned a unit value using the respective AP material as a calibrator. Polyclonal/monoclonal RM and 30 samples were evaluated for linearity, unit equivalency and commutability. Polyclonal AP material was assigned a value of 100 U IgG and 15 U IgM anti-β2 GPI, respectively. IgG-RM had a value of 270 IgG and the IgM-RM of 220.3 IgM anti-β2 GPI U. The linearity ( R 2 ) of each RM curve for the various assays ranged from 0.96 to 0.99. Commutability samples fit very well within 95% prediction intervals and had excellent correlation when comparing assays. IgG and IgM polyclonal and IgG monoclonal RM displayed excellent linearity and commutability, being good candidates for better standardization of anti-β2 GPI immunoassays.